A Control System for Robots and Wheelchairs: Its Application for People with Severe Motor Disability - Alonso, Alonso A.; Rosa, Ramón de la; Carrera, Albano; Bahillo, Alfonso; Durán, Ramón; Fernández, Patricia (IntechOpen, 2011)
None